Indoor/outdoor air quality relationship in urban commercial buildings - Challoner, Avril (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2013)
The United Nations urban environmental unit associates up to 1 million premature deaths annually to urban air pollution (United Nations Environment Programme, 2010). Much research on indoor environments has focused on residential buildings with commercial buildings being often overlooked. This research project aimed to improve the understanding of the Indoor/Outdoor air quality relationship at urban commercial buildings in Dublin, Ireland. In order to gain the required understanding, data was required for Dublin sites, therefore monitoring was conducted. Real-time concentrations of PM2.5 and NO2 were recorded at 10 commercial buildings (including shops, offices and gallery spaces) all located in heavily trafficked parts of the city centre.
Keywords: Civil, Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin